2012
DOI: 10.1007/s11033-012-2140-8
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic cadmium metallothionein gene (PMCd1syn) of Paramecium species: expression, purification and characteristics of metallothionein protein

Abstract: Metallothioneins (MTs) are metal binding proteins that are rich in cysteine residues constituting 10-30 % of the total protein, and in which the thiol groups bind to the metal ions. The increasing amount of metal ions in the medium have shown increased production of MTs by different organisms such as bacteria, protozoa and mammals like humans. PMCd1 is the first gene ever discovered in Paramecium, a ciliated protozoan, that could produce this MT in response to cadmium. In this study the PMCd1syn gene has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In our study, the results regarding concentration of metallothionein were comparable to those of Dar et al . (). Their group was interested in the production of metallothionein in various microorganisms in response to cadmium and they showed an increased accumulation of cadmium in cells expressing the protein metallothionein in comparison with control cells.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the results regarding concentration of metallothionein were comparable to those of Dar et al . (). Their group was interested in the production of metallothionein in various microorganisms in response to cadmium and they showed an increased accumulation of cadmium in cells expressing the protein metallothionein in comparison with control cells.…”
Section: Discussionmentioning
confidence: 97%
“…It can chelate with heavy metal ions through sulfhydryl groups, so that microorganisms can maintain normal growth and metabolism in an environment rich in metal ions. Some studies have shown that the expression of bacterial metallothionein will be increased, and the overexpression of metallothionein also increases the proportion of heavy metal ions chelated under high concentrations of metal ions (Mathivanan et al 2021 ; Dar et al 2013 ).…”
Section: Metal Ion Stress Response In Bioleaching Microorganisms For ...mentioning
confidence: 99%
“…However, ciliate MTs present exclusive features with regard to classic MTs: they are longer proteins (60-193 aa) having higher cysteine content (22-54 residues) and aromatic amino acids are present in several of them 48 . So far, study of MTs in ciliates has been restricted to genera Tetrahymena 47,52 and Paramecium 56 . In Paramecium sp., MT gene is not well characterized.…”
Section: Bioaccumulation Of Heavy Metals and The Role Of Metallothion...mentioning
confidence: 99%